Quark matter and quark stars - Fiolhais, M.; Linares, L. P.; Malheiro, M.; Taurines, A. [UNESP] (My University, 2004)
Strange quark matter is studied in the framework of the Chromodielectric model (CDM), and the corresponding equations of state are used to investigate the structure (mass and radius) of cosmological compact objects. At high densities, the phase of QCD known as “Color Flavour Locked” (CFL) phase, may also be modelled in the CDM through the inclusion of a direct quark-quark correlation (pairing) energy. We studied this phase, obtaining the corresponding equation of state, which we compared with the equations of state of the other phases. The results show that the equations of state obtained in the framework of the CDM are similar to those obtained in the framework of QCD. On the other hand, the CFL phase turns out to be more stable than the normal (beta equilibrium) phase. Work is still in progress regarding the structure of quark stars which are obtained using the equation of state for the CFL phase.